2008
DOI: 10.1002/apj.192
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a pore‐former and PTFE in the performance of the direct ethanol fuel cell

Abstract: The direct ethanol fuel cell (DEFC) is a promising fuel cell device, which could provide power to portable and microelectronic equipment in the future. In the present investigation, the influence of a pore-former, polytetrafluoroethylene (PTFE) and catalyst loadings in the electrocatalyst of the anode on DEFC performance is studied. The decal transfer method is used to prepare the membrane electrode assembly (MEA) using Pt-Ru/C (40 : 20% by wt) as the anode catalyst, and Pt/C (40% by wt) as the cathode catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…3, i.e., the kinetic region is not affected by changing the diffusion layer porosity while at higher currents the slope of the curve increases with decreasing porosity. Furthermore, Biswas et al [17] found better performance by increasing both the porosity and the PTFE content (20%) in the catalyst layer. However, in their case the catalyst layer was fabricated using pore formers, therefore the PTFE content could have a very different effect compared to the present work.…”
Section: Effect Of Anode Diffusion Layermentioning
confidence: 99%
See 1 more Smart Citation
“…3, i.e., the kinetic region is not affected by changing the diffusion layer porosity while at higher currents the slope of the curve increases with decreasing porosity. Furthermore, Biswas et al [17] found better performance by increasing both the porosity and the PTFE content (20%) in the catalyst layer. However, in their case the catalyst layer was fabricated using pore formers, therefore the PTFE content could have a very different effect compared to the present work.…”
Section: Effect Of Anode Diffusion Layermentioning
confidence: 99%
“…Although the CCM MEA had higher ethanol crossover rate, its performance and stability were superior compared to the GDE MEA, having a peak power degradation of 15% against 34% for the GDE MEA in a 10 h life test, which was attributed to less delamination problems in the case of the CCM MEA. The structure of the catalyst layer has also been investigated for DEFC [17]. In this work, the authors obtained higher cell performance using pore formers in the anode catalyst layer, and by increasing PTFE content in the catalyst layer from 10 to 20 wt%.…”
Section: Introductionmentioning
confidence: 98%
“…NH 4 HCO 3 was also used as a PF in the cathode CL of a DMFC, which improve the cell performance by approximately 30%. The performance enhancement obtained using PFs in a direct ethanol fuel cell was also confirmed by adding 10 wt % NaHCO 3 into the catalyst ink during MEA fabrication . The effect of the PF loading in the anode CL of a DMFC was also investigated .…”
Section: Introductionmentioning
confidence: 83%
“…Recently, studies have focused on the mass transfer behavior of the reactants inside the electrodes . To improve the mass transfer, pore formers (PFs) were incorporated into the CLs or the microporous layers to improve the performance of the fuel cell. Tucker et al enhanced the maximum power density of an active DMFC from approximately 900 to 1200 W/m 2 by adding 50 wt % Li 2 CO 3 into the anode CL as PF.…”
Section: Introductionmentioning
confidence: 99%